2022
DOI: 10.3390/molecules27175621
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Biological Activities of Amaryllidaceae Alkaloid Norbelladine Derivatives and Precursors

Abstract: Amaryllidaceae alkaloids (AAs) are a structurally diverse family of alkaloids recognized for their many therapeutic properties, such as antiviral, anti-cholinesterase, and anticancer properties. Norbelladine and its derivatives, whose biological properties are poorly studied, are key intermediates required for the biosynthesis of all ~650 reported AAs. To gain insight into their therapeutic potential, we synthesized a series of O-methylated norbelladine-type alkaloids and evaluated their cytotoxic effects on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In 2022, we studied the anti-DENV activity of norbelladine, its derivatives and its precursors. 3 We revealed that the 3,4dihydroxybenzaldehyde (selectivity index (SI) = 7.2), 3 ′ ,4 ′ -Odimethylnorbelladine (SI = 4.8), 4 ′ -O-methylnorbelladine (SI > 4.9), 3 ′ -O-methylnorbelladine (SI > 4.5), and norcraugsodine (SI = 3.2) reduced DENV infection with EC 50 values ranging from 24.1 to 44.9 mM, and the mechanism of action is currently under investigation. Barbosa et al searched for plant-derived antiviral agents against DENV and ZIKV.…”
Section: Dengue and Zika Virusesmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2022, we studied the anti-DENV activity of norbelladine, its derivatives and its precursors. 3 We revealed that the 3,4dihydroxybenzaldehyde (selectivity index (SI) = 7.2), 3 ′ ,4 ′ -Odimethylnorbelladine (SI = 4.8), 4 ′ -O-methylnorbelladine (SI > 4.9), 3 ′ -O-methylnorbelladine (SI > 4.5), and norcraugsodine (SI = 3.2) reduced DENV infection with EC 50 values ranging from 24.1 to 44.9 mM, and the mechanism of action is currently under investigation. Barbosa et al searched for plant-derived antiviral agents against DENV and ZIKV.…”
Section: Dengue and Zika Virusesmentioning
confidence: 99%
“…the relative relevance of lycorine inhibition of correct viral polyprotein translation or nucleocapsid assembly on viral inhibition, has not been measured directly, which will be crucial to verify the importance of each pharmacophore. 3 (2) Cherylline non-methylated 3 ′ OH (compared to gigantelline), and the absence of hydroxyl group on the phenol cycle C3 (compared to gigantellinine) is required for its anti-viral activity specific to RNA replication (PDB: 5WZ3). 5 (3) Lycorine C1 hydroxyl group interacts with Zika virus RNA-dependent RNA polymerase to block RNA synthesis, (as shown by in vitro enzyme assay, docking evidence, and interaction with His110).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations